Aorto-left ventricular communication after closure. Late postoperative problems. Issue 5 (May 1983) - Serino, W; Andrade, J L; Ross, D; de Leval, M; Somerville, J
Abstract : The long-term follow-up of six patients operated on for aorto-left ventricular communication has been reviewed in detail. All had residual aortic regurgitation after the initial repair of the defect. It was severe in four and required repeated reoperation in three with ultimate aortic valve replacement. The failure of early repair to solve the haemodynamic problem has provoked a reconsideration of the basic anatomy, of the surgical approach, and of the postoperative physiology of this anomaly. The so called "tunnel" is not a tunnel with length but should be considered as a localised breach at the insertion of the right coronary cusp. The localised aortic root dilatation at the site is a weakness that remains after closure of the tunnel leaving a poorly supported aortic valve and a weak root. Thus, the initial repair of the aorto-left ventricular communication must not only close the communication but reinforce, strengthen, and support the right aortic sinus in order to maintain cusp competence.